Computer interrogation of patients. Issue 6036 (11th September 1976) - Lucas, R W; Card, W I; Knill-Jones, R P; Watkinson, G; Crean, G P
Abstract : A system of routine interrogation of patients using a computer has been developed. It includes a visual display unit with a specially designed response keyboard, and the program has been designed to adapt to the individual patient. The system was evaluated objectively, using the criteria of accuracy in eliciting symptoms, acceptability to the patient, and cost. While doctors will always take the ultimate management decisions, it seems that machines can be programmed to undertake the routine interrogation of patients, elicit evidence accurately and acceptably, and calculate the probabilities of disease as effectively as doctors.